Origin of Islamophobia in Europe: A Case Study of Hungary - Apipudin; Alwi Alatas (Journal of Islamic Thought and Civilization, 2024)
The attack on the World Trade Center (WTC) in 2001 proved to be a turning point in the relationship between Islam and the West. Subsequently, the United States (US) invaded Iraq to avenge the tragedy. The US called its militaristic venture into the Middle East as an "act against terror." This invasion triggered a political crisis in the Middle Eastern countries. This situation was further aggravated by the Arab Spring, which occurred in the Middle East in 2011. The Arab Spring created problems in Syria, Iraq, Egypt, and Tunisia. Political instability in the Middle East has forced Arab people to immigrate to European countries. The increase in Arab immigrants in the early 21st century fueled Islamophobia in Europe. Hungary is one of the European countries that has accepted many Arab immigrants. This studydiscusses the relationship between the rise of Arab migration and the increase of Islamophobia in Europe, particularly in Hungary. A qualitative research approach was used to analyse various government and non-government reports and literature. This study argues that the increasing population of Arab immigrants in Europe has led to the emergence of right-wing political movements. These movemnets play a major role in carrying out Islamophobic propaganda in European  social and cultural life.